A Sala de Recursos Multifuncional: a proposta oficial para o trabalho docente frente às necessidades educacionais dos alunos com deficiência intelectual - Pertile, Eliane Brunetto (2014)
The present study aimed to understand the proposal released by the Ministry of Education (MEC) for teaching work in Rooms Multifunction Resources (SRM), with students with intellectual disabilities. The survey was conducted through documentary and bibliographical study. On desk research, we selected regulations that establish special education in inclusive perspective and guiding materials for pedagogical issues, published by the MEC. The literature, in turn, made the analysis of these documents by understanding the social context that determines the depth and specificity on the development of people with intellectual disabilities, through the prism of Historical-Cultural Theory. We undertook an analysis of the underlying language meanings expressed in the documents as identification of intentionality that they serve. We understand that this approach is relevant considering that the SRM was disseminated nationally, gained prominence in referrals for special education in inclusive perspective and constituted as an official proposal to meet students, with priority space for the realization of Specialized Educational Services (ESA ). The study had developed the understanding that the argumentative framework expressed by advisors, published and disseminated by the MEC documents, is compatible with these principles in constructivist theory, presents a conception of human development spontaneist, sustained a biological understanding, the learner's own regulates their development and thus empties the mediations inherent in the process of schooling, since devalues school content and the act of teaching. Based on the research that we use, it was possible to understand that such guidelines are consistent with the formation of the right man for the composition of the workforce updated with the requirements of the contemporary production process. Thus, they predict a unilateral training with restricted and immediate acquisition of skills targeted at the work. We understand, therefore, that once they are in agreement with the demands of training expected to reproduction of existing conditions, the proposals for the teaching job does not converge to the humanization of individuals with intellectual disabilities